2000
DOI: 10.1021/jp002313m
|View full text |Cite
|
Sign up to set email alerts
|

σ Bond Activation by Cooperative Interaction with ns2 Atoms:  Be + nH2, n = 1−3

Abstract: Ab initio investigations at the MP2, CCSD(T), and MRCISD levels of theory with augmented triple-basis sets have identified and characterized various stationary points on the Be/(H 2 ) n , n ) 1-3, hypersurfaces. The van der Waals complexes, Be(H 2 ) n , are very weakly bound (D e ) 0.08-0.32 kcal/mol with respect to H 2 loss) with H 2 /H 2 interactions playing an important role in determining equilibrium structures which can be understood in terms of the various relevant long-range potentials. The covalent mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…1. 38 This model has been used extensively in the literature 6,28,[39][40][41][42][43][44] to test new multireference methods since it is a prototype for symmetry forbid- den reactions. 45 In the BeH 2 model, the reaction coordinate is parametrized by a one-dimensional variable x that falls in the range [0,4] bohrs.…”
Section: A Beh 2 Model Cas(22)mentioning
confidence: 99%
“…1. 38 This model has been used extensively in the literature 6,28,[39][40][41][42][43][44] to test new multireference methods since it is a prototype for symmetry forbid- den reactions. 45 In the BeH 2 model, the reaction coordinate is parametrized by a one-dimensional variable x that falls in the range [0,4] bohrs.…”
Section: A Beh 2 Model Cas(22)mentioning
confidence: 99%
“…Subsequent theoretical studies on the isoelectronic Li -+ nH 2 and Be + nH 2 systems 4,5 and the isovalent Al + + nH 2 system 3 sought to identify how much of the activation energy lowering in the cooperative interaction mechanism could be attributed to the node structure of the orbitals, how much to the effect of the positive charge and relative bond strengths, and how much to the special ability of boron to form three-center two-electron bonds (3c-2e). The results revealed that (1) the n ) 1 activation energy was dominantly controlled by M-H bond energy, (2) the positive charge and HM-H bond energy play important roles in the activation energy lowering occurring for n ) 2, and (3) 3c-2e bonding played a small role in the n ) 3 case.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of sigma bonds, particularly CH sigma bonds, is an active area of experimental and theoretical research and has been referred to as one of the "Holy Grails" of modern chemical research. 1 Recent theoretical studies [2][3][4][5][6] have identified a new mode of sigma bond activation that depends critically on the number of sigma bonds simultaneously interacting with an atom in an s 2 electron configuration. Motivated by unexpected experimental results, 7 theoretical studies 2 of this cooperative interaction mechanism first focused on the gas phase reactions: B + ( 1 S g ) + nH 2 f BH 2 + + (n -1)H 2 , n ) 1-4.…”
Section: Introductionmentioning
confidence: 99%